Enhancing Understanding of Boyle’s Law through the Use of Simple Teaching Aids - Anugrah, Adyt; Fitri, Megawati Ridwan; Hamatun, Hamatun (Smart Society, 2024)
Conceptual understanding in physics is often a challenge for students, especially in abstract topics such as Boyle's Law in the kinetic theory of gases. This study aims to analyze the effect of using simple teaching aids in enhancing students understanding of Boyle's Law. The research employed a quasi-experimental method with a one-group pretest and posttest design. The study involved 34 high school students selected through simple random sampling. Data were collected through a conceptual understanding test administered before and after the implementation of the Boyle's Law teaching aid. The results showed a significant increase in the average posttest score (78.13) compared to the pretest score (38.27), with a decrease in standard deviation from 9.59 to 4.23. The N-Gain score of 0.68 indicates that the improvement in students understanding falls within the moderate category. These findings suggest that simple teaching aids can help bridge the gap between abstract concepts in Boyle's Law and students concrete experiences, thereby enhancing their conceptual understanding. This indicates that the use of simple teaching aids can be an effective instructional strategy for teaching abstract physics concepts, particularly Boyle's Law.